2021
DOI: 10.17223/17267080/78/7
|View full text |Cite
|
Sign up to set email alerts
|

Online Short Spatial Ability Battery (OSSAB): Psychometric Norms for Older Students

Abstract: The need for STEM specialists is growing in current technologically-oriented economy. This calls for new approaches in evaluation and development of relevant abilities and skills. However, the current educational systems might miss some students who have high potential for this field or who can develop such potential. For example, according to the results of one Russian study, gifted children may be missed by existing methods of talent search, partially due to the lack of standardised psychometric tests, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The distribution of the OSSAB total score was close to normal (see Figure 1); skewness and kurtosis varied within the acceptable range (from -2 to +2). The mean for the OSSAB total score was 52.99 (SD = 17.29) -very similar to that previously reported for adolescents (Mean = 51.02; SD = 20.02) [44]. The descriptive statistics for the OSSAB subtests (Shape Rotation, Mechanical Reasoning, Paper Folding, and Pattern Assembly) are presented in Table 2.…”
Section: Descriptive Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…The distribution of the OSSAB total score was close to normal (see Figure 1); skewness and kurtosis varied within the acceptable range (from -2 to +2). The mean for the OSSAB total score was 52.99 (SD = 17.29) -very similar to that previously reported for adolescents (Mean = 51.02; SD = 20.02) [44]. The descriptive statistics for the OSSAB subtests (Shape Rotation, Mechanical Reasoning, Paper Folding, and Pattern Assembly) are presented in Table 2.…”
Section: Descriptive Analysissupporting
confidence: 80%
“…Two recent studies also used these 4 tests in university student samples as part of larger SA battery, showing good psychometric properties and robust correlations with other SA tests (on a Russian sample by E. Esipenko et al [42], on Russian and Chinese samples by M. V. Likhanov et al [43]). Later, M. V. Likhanov and colleagues developed psychometric norms for the use of the OSSAB with Russian schoolchildren and provided recommendations for adolescents with different levels of SA [44].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…e logical starting point for behavioral measurement is James Lange's Emotional Body eory [21]. is theory believes that human emotions are caused by physical changes, and emotions are generated after physiological and behavioral changes [22][23][24].…”
Section: Related Workmentioning
confidence: 99%
“…Another study showed that training of visuospatial working memory and spatial reasoning enhanced maths learning in a randomized study of 17 thousand children (Judd & Klingberg, 2021). While there are some attempts to include spatial ability in educational systems (Castro‐Alonso & Uttal, 2019; Kell et al, 2013; Likhanov et al, 2021; Stieff et al, 2014; Stieff & Uttal, 2015), it is important to further explore the nature of spatial ability and identify potential aims for interventions.…”
Section: Introductionmentioning
confidence: 99%